INNOVATIVE DESIGN METHODOLOGY FOR MUSIC EDUCATION BASED ON THE NEW UZBEKISTAN DEVELOPMENT STRATEGY (Web of Teachers: Inderscience Research, 2026)
The New Uzbekistan Development Strategy is enriching the education system in our country with modernity, openness, and innovative approaches, along with all other sectors. In this process, improving the quality of music education, introducing modern methods into the content of education, and creating a favorable environment for the development of students' creative and artistic thinking have become urgent issues today. Based on the concept of the New Uzbekistan, approaches to music education are being updated not only in a traditional way, but also in accordance with the needs of modern development. This article thoroughly analyzes the innovative design methodology of the music education process, its importance and effectiveness, new perspectives, and practical recommendations.